TOWARDS SUSTAINABLE TOURISM: DESIGNING A SUSTAINABLE SUPPLY CHAIN STRATEGY FOR THE TOURISM INDUSTRY THROUGH THE INTEGRATION OF FUZZY AHP AND PLS-SEM - Wardana, M. Azka Kesuma; Agustin, Maulina; Pandiangan, Camaro (Jurnal Bisnis dan Keuangan, 2025)
This study examines the implementation strategy of Sustainable Supply Chain Management (SSCM) in the tourism industry by integrating economic, social, environmental, and institutional dimensions. The research aims to formulate data-driven strategic priorities. A quantitative approach using SEM-PLS was employed to analyze causal relationships, and Fuzzy AHP to rank sustainability priorities. Results indicate that environmental, social, and institutional sustainability positively affect SSCM, while economic sustainability has a negative influence. Fuzzy AHP ranks environmental sustainability as the top priority. The findings highlight the need for policy alignment, community involvement, and business commitment to build competitive and sustainable tourism destinations.